+0  
 
0
110
1
avatar+452 

Help.

NotSoSmart  Apr 7, 2017
Sort: 

1+0 Answers

 #1
avatar+75279 
+1

 

The tangent forms a right triangle.....AO  is the hypotenuse and AB is a leg....so.....by the Pythagorean Theorem......

 

r  = sqrt ( AO^2 - AB^2)  = sqrt ( 11.7^2 - 6^2 )   = sqrt ( 136.89 - 36) =

 

sqrt (  100.89) ≈  10.04  =  10 .0  (rounded)

 

 

cool cool cool

CPhill  Apr 7, 2017

17 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details